Finance sources, challenges and allocations of working students in U.P. Diliman - Cherreguine, Haniel Lalas (College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT The researchers undertook this study considering the observation that there is an increasing number of U.P. working students in Diliman Campus. Working part-time implies that these students need to augment their financial needs to sustain their schooling. Also, a previous study (Sembrano, 2010) states that only 50% of working students get to finish college because many of them cannot cope and cannot concentrate on their studies while others give up because of insufficient funds. The study focused on determining the sources of finances of U.P. Diliman working students, where do they allocate their finances, what are the challenges and problems being encountered, and how do they overcome these challenges and problems. Survey questionnaires were used to gather data from thirty (30) working students considering different student-year levels; second, third, fourth, and fifth. 15 males and 15 females were chosen respondents wherein all brackets in the STFAP (A, B, C, D, E1 and E2) have been included. Respondents were randomly chosen in dorms, libraries, and corridors of various colleges or departments. Analysis was done on the content of answers to the questions in which corresponding tables and figures presented reflect the results. Data gathered from the respondents clearly identified that the main source of income come from allowances and salaries, while 70% or 21 out of 30 allocate their finances mostly for foods and school needs. Half of the respondents follow a system in allocating their finances. Major challenges identified are (1) that their allocations being not strictly followed, (2) that of temptations, and (3) insufficient fund. Twenty (20) or those from STFAP brackets C, D, E1, and E2 have problems on delayed salary, delayed stipend, conflict with academics, and unstable working period. The challenges and problems having been known, some recommendations are given. These are particularly on the different areas of concern on allocations of finances, and on sources of finances. Hopefully, with the favorable consideration of the recommendations, more U.P. Diliman working students can survive to finish their college education and that more less-fortunate and less-privileged students will be motivated and encouraged to go through with their education.